(untitled) (Biological Sciences - PJSIR, 2003)
Imipramine hydrochloride [IPM·HCl] and promethazine hydrochloride [PMT·HCl] were used for the spectrophotometric determination of gold (III) in the aqueous solution. The halides complexes of gold (III) created a coloured coupling with the studied drugs which were extractable in chloroform. These new compounds were characterised by IR, UV-VIS spectra and thermal and elemental analysis. Rapid and sensitive spectrophotometric method for the determination of gold (III) in the aqueous solution is described. The absorbance was found to be linear function of the gold (III) concentration in the range from 0.2 to 20 x 10-1 mg. The ratio of complex [AuX4]- to the organic cation from drug in the obtained compounds was determined as 1:1. The method was satisfactorily applied to the analysis of gold (III). A great advantage of the proposed method is that the trace amounts of gold (III) can also be examined.